Driving trains, juggling lives: A review on work-life balance of Indian loco-pilots - Ranjan, Rajesh; Prasad, T; Singh, Rashmi; Tripathi, Saumya (Edelweiss Applied Science and Technology, 2025)
Loco-pilots (railway drivers) in India operate in a highly demanding and challenging work environment. Their job involves working in isolation, limited social interaction, and the immense responsibility of ensuring both safety and punctuality while running the train. The role demands constant alertness, mental resilience, and the ability to adapt to unpredictable conditions. Loco-pilots have little control over how their work is carried out, as it is largely dictated by strict timetables and technical constraints like train type and track routes. One of the major challenges they face is maintaining a balance between work and personal life. Long working hours, irregular and inflexible schedules, and a heavy workload often lead to work-family conflict and increased stress levels. While much of the existing research on work-life balance focuses on corporate employees, this study aims to shift that focus to the unique experiences of Indian railway drivers. This review provides a comprehensive look at the lives of loco-pilots, highlighting the key factors that contribute to their work-life imbalance—factors that can even impact safety and increase the likelihood of accidents. It also explores the broader implications of these working conditions on their overall well-being, productivity, and the growth of Indian Railways. The paper briefly reviews essential concepts related to work-life balance, emphasizing the urgent need to address this issue among railway drivers.